1990
DOI: 10.1002/ana.410280516
|View full text |Cite
|
Sign up to set email alerts
|

A follow‐up study of intractable seizures in childhood

Abstract: One hundred forty-five children with seizures that were refractory to medical therapy for at least 2 years were followed 5 to 20 years after onset. The majority of children with uncontrollable seizures (61%) were mentally retarded, and most of these (73%) had onset of seizures at younger than 2 years of age. Age of onset was significantly later (mean 5.0 +/- 0.5 yr [SEM]) in the group of children with borderline to normal intelligence. Follow-up data showed remission of seizures in a significant proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
97
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(119 citation statements)
references
References 47 publications
17
97
0
5
Order By: Relevance
“…In a previous study of the same childhood population (17), we reported that SE did not imply an increased risk of SMR or other additional major neuroimpairments, but SE occurred significantly more frequently in children with intractable epilepsy than in those with controlled epilepsy. Tonic, myoclonic, and atonic seizures and atypical absences are commonly reported to be frequent in intractable epilepsy, as is a low level of partial seizures (34,48). This was also the case in the univariate comparison.…”
Section: Discussionsupporting
confidence: 59%
“…In a previous study of the same childhood population (17), we reported that SE did not imply an increased risk of SMR or other additional major neuroimpairments, but SE occurred significantly more frequently in children with intractable epilepsy than in those with controlled epilepsy. Tonic, myoclonic, and atonic seizures and atypical absences are commonly reported to be frequent in intractable epilepsy, as is a low level of partial seizures (34,48). This was also the case in the univariate comparison.…”
Section: Discussionsupporting
confidence: 59%
“…Medically intractable epilepsy is a common condition among children. The tragic consequence of this condition is its effect on the brain, causing recurring seizures throughout the person's life (Huttenlocher and Hapke, 1990;Berg et al, 2006). Neonates and infants are at the highest risk of developing seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal brain injury following acute neurological disorders such as status epilepticus, encephalopathy and stroke often leads to excitotoxicity and long-term neurological perturbations, including motor and mental deficits, learning disabilities, mental retardation and/ or epilepsy (Huttenlocher and Hapke, 1990;Ferriero, 2004). While the effects of brain injury, especially from excitotoxicity, have been well studied in mature neurons in vivo and in vitro (Lipton, 1999;Sattler and Tymianski, 2001;Contestabile, 2002), the mechanisms mediating responses to excitotoxic challenge in immature neurons remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, despite increased spontaneous excitability, the immature brain undergoes less cell death than the mature brain after seizures of identical magnitude (Rennie, 1997;Sperber et al, 1997). It is unclear how immature neurons survive concentrations of excitatory compounds that are lethal to mature neurons, and whether in the absence of cell death, neuronal differentiation is impaired by the changes in the developmental patterns of activity, which could in turn result in later cognitive or motor neurological deficits (Huttenlocher and Hapke, 1990;Holmes et al, 2002;Ferriero, 2004).…”
Section: Introductionmentioning
confidence: 99%